Affective, cognitive, and metamemory effects on the estimation of the solution correctness and the feeling of satisfaction from it - Μεταλλίδου Παναγιώτα; Ευκλείδη Αναστασία (Psychology: the Journal of the Hellenic Psychological Society, 2020)
ABSTRACT IS AVAILABLE IN THE PDF